Comparative effects of EXG and conventional therapies on muscle strength and balance in older people: A meta-analysis and meta-regression - Herrera-Valenzuela, T (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This systematic review with meta-analysis aimed to analyze the effects of exergaming (EXG) versus conventional therapies on muscle strength, balance, and fear of falling in healthy older people. A systematic literature search was conducted in six generic databases (PubMed, Medline, CINAHL Complete, Scopus, Cochrane Library, and Web of Science) with no start date restrictions until May 2025. The PRISMA, TESTEX, Rob 2 and GRADE tools were used to assess the methodological quality and certainty of evidence. The protocol was registered in PROSPERO (code: CRD420251037541). From 3224 records, 25 randomized controlled trials with 2078 participants (>= 80% female) with a mean age of 71.5 +/- 5.8 years were included. Seven overall and 10 subgroup meta-analysis revealed significant improvements (p < 0.05) in favor of EXG in the timed up-and-go (TUG), 8-TUG, maximal isometric handgrip strength (MIHS) and 30-s chair stand tests. However, in the subgroup analyses of the TUG test, significant improvements (p < 0.05) were reported in favor of EXGs according to the type of console and games with very long effects (ES = 1.42-2.56) and training dosage (ES = 2.07-2.77), with improvements in only the training frequency >= 3 sessions per week (ES = 2.91). For the 30-s chair stand test, there were significant improvements (p < 0.05) in favor of EXG according to training dosage with very large effects (ES = 1.42-2.49). For meta-regression, only minutes per session in a 30-s chair stand test were presented as predictors of relapse in this test (R-2 = 0.43; p = 0.02). In conclusion, EXG is an effective alternative for improving muscle strength and balance performance in healthy older people.